ANALISIS KEBIJAKAN PEMERINTAH TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI DI KOTA YOGYAKARTA - Putra, Chanda Vedalla; Tan, Charles; Jason, Jason; Styvani, Sherlyca; Tarekar, Windy Wihue (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
The purpose of this study is to analyze the data found on the level of unemployment and inflation as well as the causes of the increase or decrease in the number of unemployment and inflation in the Yogyakarta region. Yogyakarta is a well-known city in Indonesia. The author analyzes using descriptive research methods and quantitative approaches by looking at existing data through the official website of the Yogyakarta Central Bureau of Statistics. Based on the research that has been done, the results obtained are that the highest increase in the number of unemployment increases occurred in 2020 but inflation has decreased in that year, this is due to the pandemic that has hit almost all countries in the world. Therefore, it can be concluded that the unemployment rate can affect inflation.